2020
DOI: 10.3389/fnut.2020.580550
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Household Cooking Techniques on African Nightshade and Chinese Cabbage on Phenolic Compounds, Antinutrients, in vitro Antioxidant, and β-Glucosidase Activity

Abstract: Different household cooking techniques (boiling, steaming, stir frying, and microwave) were tested on the changes of targeted phenolic compounds, antioxidant property (ferric reducing-antioxidant power (FRAP) activity), α-glucosidase activity, antinutritive compounds, and sensory properties in commonly consumed traditional leafy vegetables in Southern Africa, the non-heading Chinese cabbage (Brassica rapa L. subsp. chinensis) and African nightshade (Solanum retroflexum Dun). Stir frying increased kaempferol-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Stir-frying can lead to an increase in 4-caffeoylquinic acid due to the isomerisation and transformation of 5-caffeoylquinic acid (chlorogenic acid) [20]. Managa et al [10] also found 4-caffeoylquinic acid during all cooking methods, with stir-frying having the highest concentration. Due to isomerisation and transmutation of 5-caffeoylquinic acid, high temperatures also caused an increase in 4-O-caffeoylquinic acid levels in artichoke [21].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Stir-frying can lead to an increase in 4-caffeoylquinic acid due to the isomerisation and transformation of 5-caffeoylquinic acid (chlorogenic acid) [20]. Managa et al [10] also found 4-caffeoylquinic acid during all cooking methods, with stir-frying having the highest concentration. Due to isomerisation and transmutation of 5-caffeoylquinic acid, high temperatures also caused an increase in 4-O-caffeoylquinic acid levels in artichoke [21].…”
Section: Resultsmentioning
confidence: 98%
“…Samples of freeze-dried African pumpkin leaves (50 mg) were dissolved in ethanol/water (70:30, v/v), ultrasonicated for 30 min and centrifuged at 1000× g for 20 min at 4 • C. The extraction was repeated, and the supernatants were pooled together before filtering using polytetrafluorethylene filters, as described by Managa et al [10].…”
Section: Extraction Of Phenolic Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Boiling and stir-frying improve palatability and reduce antinutrients in nightshade, such as tannin, as opposed to the raw vegetable (Managa et al, 2020;Sivakumar et al, 2020). Cooking also eliminates risks of bacterial or fungal contamination while not reducing the anticancerogenic properties of nightshade (Odongo et al, 2018).…”
Section: Distribution and Marketingmentioning
confidence: 99%
“…Moreover, the general contribution of bush beans and nightshade to local diets and health should be investigated further. For example, nightshade, while being rich in vitamins, seems to be most interesting for its bioactive plant compounds, including anticancerogenic and antidiabetic values (Managa et al, 2020;Moyo et al, 2018;Odongo et al, 2018). Locals might not know the exact nutrient components of nightshade, but they are well aware of its general health benefit which often motivates nightshade cultivation.…”
Section: Quality and Economic Lossesmentioning
confidence: 99%